Systemic Upregulation of IL-10 (Interleukin-10) Using a Nonimmunogenic Vector Reduces Growth and Rate of Dissecting Abdominal Aortic Aneurysm. Issue 8 (August 2018) - Adam, Matti; Kooreman, Nigel Geoffrey; Jagger, Ann; Wagenhäuser, Markus U.; Mehrkens, Dennis; Wang, Yongming; Kayama, Yosuke; Toyama, Kensuke; Raaz, Uwe; Schellinger, Isabel N.; Maegdefessel, Lars; Spin, Joshua M.; et al.
Abstract : Objective—: Recruitment of immunologic competent cells to the vessel wall is a crucial step in formation of abdominal aortic aneurysms (AAA). Innate immunity effectors (eg, macrophages), as well as mediators of adaptive immunity (eg, T cells), orchestrate a local vascular inflammatory response. IL-10 (interleukin-10) is an immune-regulatory cytokine with a crucial role in suppression of inflammatory processes. We hypothesized that an increase in systemic IL-10-levels would mitigate AAA progression. Approach and Results—: Using a single intravenous injection protocol, we transfected an IL-10 transcribing nonimmunogenic minicircle vector into the Ang II (angiotensin II)-ApoE −/− infusion mouse model of AAA. IL-10 minicircle transfection significantly reduced average aortic diameter measured via ultrasound at day 28 from 166.1±10.8% (control) to 131.0±5.8% (IL-10 transfected). Rates of dissecting AAA were reduced by IL-10 treatment, with an increase in freedom from dissecting AAA from 21.5% to 62.3%. Using flow cytometry of aortic tissue from minicircle IL-10-treated animals, we found a significantly higher percentage of CD4 + /CD25 + /Foxp3 (forkhead box P3) + regulatory T cells, with fewer CD8 + /GZMB + (granzyme B) cytotoxic T cells. Furthermore, isolated aortic macrophages produced less TNF-α (tumor necrosis factor-α), more IL-10, and were more likely to be MRC1 (mannose receptor, C type 1)–positive alternatively activated macrophages. These results concurred with gene expression analysis of lipopolysaccharide-stimulated and Ang II-primed human peripheral blood mononuclear cells. Conclusions—: Taken together, we provide an effective gene therapy approach to AAA in mice by enhancing antiinflammatory and dampening proinflammatory pathways through minicircle-induced augmentation of systemic IL-10 expression. Abstract : Supplemental Digital Content is available in the text.